Psychoanalysis and passion: the position of the subject - Dasuky Quiceno, Samir A.; Mejía Mejía, Alejandra; Rivera Botero, Gloria; Martinez Acebedo, Daniel; Fernández Jaramillo, Luz I. (Informes Psicológicos, 2009)
This article is the result of a conceptual investigation, from the psychoanalytic perspective, to show how in the conception of mental illness, Freud introduces the dimension of the subject with regard to the drive-passion in the formation of neurosis. Freud, of medical-psychiatric training, receives from his tradition some etiological conceptions of the disease in two main ways: The conception of the disease by way of external and internal accidents and by a hereditary or predisposing conception of the disease, of which Freud distances himself to think of mental illness as a psychic reality, introducing the responsibility of the subject for his own discomfort, as a product of conflicts that are generated in relation to the drive -passion in the sexual order.